Oral levosimendan in amyotrophic lateral sclerosis: A phase II multicentre, randomised, double-blind, placebo-controlled trial - Hardiman, Orla (My University, 2019)
Objective: To evaluate the efficacy and safety of oral levosimendan in patients with amyotrophic lateral sclerosis (ALS). This phase II, randomised, double-blind, placebo-controlled, crossover, three-period study with 6 months open-label follow-up enrolled adults with ALS and sitting slow vital capacity (SVC) 60%–90 % of predicted from 11 sites in four countries. Methods: Patients received levosimendan 1 mg daily, 1 mg two times a day or placebo during three 14-day crossover periods and levosimendan 1–2 mg daily during open-label follow-up. Primary endpoint was sitting SVC; secondary endpoints included supine SVC, ALS Functional Rating Scale-Revised (ALSFRS-R), tolerability and safety. Results: Of 66 patients randomised, 59 contributed to the double-blind results and 50 entered open-label follow-up. Sitting SVC was not significantly different between the treatments. In post hoc analysis using period-wise baselines, supine SVC favoured levosimendan over placebo, estimated mean differences from baseline being −3.62% on placebo, +0.77% on levosimendan 1 mg daily (p=0.018) and +2.38% on 1 mg two times a day (p=0.001). Headache occurred in 16.7% of patients during levosimendan 1 mg daily (p=0.030), 28.6% during 1 mg two times a day (p=0.002) and 3.3% during placebo. The respective frequencies for increased heart rate were 5.1% (p=0.337), 18.5% (p=0.018) and 1.7%. No significant differences between the treatments were seen for other adverse events. Conclusions: Levosimendan did not achieve the primary endpoint of improving sitting SVC in ALS. Headache and increased heart rate were increased on levosimendan, although it was otherwise well tolerated. A phase III study to evaluate the longer term effects of oral levosimendan in ALS is ongoing.
Keywords: Amyotrophic lateral sclerosis (ALS); Levosimendan; Sitting slow vital capacity (SVC)